Detection of prostate cancer in unselected young men: prospective cohort nested within a randomised controlled trial. Issue 7630 (15th November 2007) - Lane, J Athene; Howson, Joanne; Donovan, Jenny L; Goepel, John R; Dedman, Daniel J; Down, Liz; Turner, Emma L; Neal, David E; Hamdy, Freddie C
Abstract : Objective To investigate the feasibility of testing for prostate cancer and the prevalence and characteristics of the disease in unselected young men. Design Prospective cohort nested within a randomised controlled trial, with two years of follow-up. Setting Eight general practices in a UK city. Participants 1299 unselected men aged 45-49. Intervention Prostate biopsies for participants with a prostate specific antigen level of 1.5 ng/ml or more and the possibility of randomisation to three treatments for those with localised prostate cancer. Main outcome measures Uptake of testing for prostate specific antigen; positive predictive value of prostate specific antigen; and prevalence of prostate cancer, TNM disease stage, and histological grade (Gleason score). Results 442 of 1299 men agreed to be tested for prostate specific antigen (34%) and 54 (12%) had a raised level. The positive predictive value for prostate specific antigen was 21.3%. Ten cases of prostate cancer were detected (2.3%) with eight having at least two positive results in biopsy cores and three showing perineural invasion. One tumour was of high volume (cT2c), Gleason score 7, with a positive result on digital rectal examination; nine tumours were cT1c, Gleason score 6, and eight had a negative result on digital rectal examination. Five of the nine eligible participants (55%) agreed to be randomised. No biochemical disease progression in the form of a rising prostate specific antigen level occurred in two years of follow-up. Conclusions Men younger than 50 will accept testing for prostate cancer but at a much lower rate than older men. Using an age based threshold of 1.5 ng/ml, the prevalence of prostate cancer was similar to that in older men (3.0 ng/ml threshold) and some cancers of potential clinical significance were found. Trial registration Current Controlled Trials ISRCTN20141297